Soil carbon sequestration and land use change associated with biofuel production: empirical evidence - Qin, Zhangcai; Dunn, Jennifer B.; Kwon, Ho Young; Mueller, Steffen; Wander, Michelle M. (Wiley, 2016)
Soil organic carbon (SOC) change can be a major impact of land use change (LUC) associated with biofuel feedstock production. By collecting and analyzing data from worldwide field observations of majorLUCs from cropland, grassland, and forest to lands producing biofuel crops (i.e. corn, switchgrass,Miscanthus, poplar, and willow), we were able to estimateSOCresponse ratios and sequestration rates and evaluate the effects of soil depth and time scale onSOCchange. Both the amount and rate ofSOCchange were highly dependent on the specific land transition. Irrespective of soil depth or time horizon, cropland conversions resulted in an overallSOCgain of 6–14% relative to initialSOClevel, while conversion from grassland or forest to corn (without residue removal) or poplar caused significant carbon loss (9–35%). No significantSOCchanges were observed in land converted from grasslands or forests to switchgrass,Miscanthus,or willow. TheSOCresponse ratios were similar in both 0–30 and 0–100 cm soil depths in most cases, suggestingSOCchanges in deep soil and that use of top soil only forSOCaccounting in biofuel life cycle analysis (LCA) might underestimate totalSOCchanges. Soil carbon sequestration rates varied greatly among studies and land transition types. Generally, the rates ofSOCchange tended to be the greatest during the 10 years following land conversion and had declined to approach 0 within about 20 years for mostLUCs. Observed trends inSOCchange were generally consistent with previous reports. Soil depth and duration of study significantly influenceSOCchange rates and so should be considered in carbon emission accounting in biofuelLCA. High uncertainty remains for many perennial systems and forest transitions, additional field trials, and modeling efforts are needed to draw conclusions about the site‐ and system‐specific rates and direction of change.